Exploring the use of technology-mediated peer learning: EFL instructors’ perspective - Wagdi Rashad Ali Bin-Hady; Abduljalil Nasr Hazaea; Amal Abdelsattar Metwally; Jamal Kaid Mohammad Ali; Mohammad Abdullah Alhammad (Studies in English Language and Education, 2026)
As digital technologies reshape educational practices, peer learning has gained renewed attention for its potential to promote collaboration, autonomy, and language development. Peer learning is recognized as an innovative learning strategy for its ability to enhance student learning outcomes, foster autonomy, and promote collaboration. This study responded to the rapid influx of digital technologies by introducing a pedagogical model, Technology-Mediated Peer Learning (TMPL), designed to foster peer interaction among students learning English as a Foreign Language (EFL). Using a qualitative approach, this study examined how EFL instructors used educational technologies in diverse global contexts to facilitate peer-based learning. More specifically, the study addresses two research objectives: (a) to identify the types of learning technologies (LTs) that EFL instructors can employ to enhance peer learning, and (b) to explore the mechanisms through which educational technologies facilitate peer learning among EFL students. Data were collected from 30 EFL instructors across different countries through an online discussion initiated on ResearchGate and LinkedIn. The data were thematically analyzed, revealing four core strategies EFL instructors employ to promote TMPL: using digital platforms, leveraging online resources, integrating multimedia tools, and designing collaborative activities. The analysis further demonstrates that these strategies can be operationalized through several educational technology functions, namely facilitating student interaction, fostering collaboration, enhancing communication, and developing language skills. Collectively, the study introduces TMPL as a unified model that functions as a dynamic mechanism for promoting student-centered learning, effectively bridging peer learning theory and digital technology. The study encourages EFL instructors to use technology as an active mediator of peer interaction, facilitate collaborative meaning-making, and enhance language skills through sustained, technology-mediated peer engagement in authentic learning contexts.